2014
DOI: 10.1038/leu.2014.310
|View full text |Cite
|
Sign up to set email alerts
|

IL-35 mitigates murine acute graft-versus-host disease with retention of graft-versus-leukemia effects

et al.

Abstract: IL-35 is a newly discovered inhibitory cytokine secreted by regulatory T cells (Tregs) and may have therapeutic potential in several inflammatory disorders. Acute graft-versus-host disease (aGVHD) is a major complication of allogeneic hematopoietic stem cell transplantation and caused by donor T cells and inflammatory cytokines. The role of IL-35 in aGVHD is still unknown. Here we demonstrate that IL-35 overexpression suppresses CD4+ effector T cell activation, leading to a reduction in alloreactive T-cell res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…As an anti-inflammatory and immune inhibitory cytokine, IL-35 has been demonstrated to suppress T cell proliferation [1], convert naive T cells into IL-35-producing iTr35 [8], and play important roles in inflammatory diseases [910], infectious diseases [5, 1112], autoimmune diseases [1316], and allograft rejection [1718]. …”
Section: Introductionmentioning
confidence: 99%
“…As an anti-inflammatory and immune inhibitory cytokine, IL-35 has been demonstrated to suppress T cell proliferation [1], convert naive T cells into IL-35-producing iTr35 [8], and play important roles in inflammatory diseases [910], infectious diseases [5, 1112], autoimmune diseases [1316], and allograft rejection [1718]. …”
Section: Introductionmentioning
confidence: 99%
“…However, in another study in the same CIA model, a regulatory T cell subset characterized by CD4 and CD39 but not Foxp3 expression was demonstrated being capable of conferring protection upon treatment with exogenous IL-35 [12]. In a model of acute graft-versus-host disease, IL-35 overexpression in target organs mitigated the disease via induction of Foxp3 + Treg cells [47]. We therefore investigated whether IL-35, ectopically expressed by DCs, could also increase Treg cell populations in the NOD diabetes model.…”
Section: Dcs Ectopically Expressing Il-35ig Protect From the Developmmentioning
confidence: 93%
“…Liu et al have reported that IL-35 has an important role in reducing acute graft-versus-host disease (a-GVHD) through promoting the expansion of Tregs and repressing Th1 responses, and should be investigated as therapeutic strategy for a-GVHD [19]. Zhang et al have reported that IL-35 may affect the development of a-GVHD by inhibiting platelet activation and aggregation, suggesting that IL-35 represents a potentially effective therapeutic agent against a-GVHD after allogeneic hematopoietic stem cell transplantation (allo-HSCT) [20].…”
Section: Suppression Of T-cell Proliferation (2) Conversion Of Naivementioning
confidence: 99%